Internet Usage among Graduate Students of Institutions of Higher Learning - The Role of Questions in Initial Web Search Strategy - Jayaraj, Vijaya Kumar (2004)
This research employs both qualitative and quantitative methodology to analyze differences between graduate students studying in four leading public universities and their choice of initial Web search strategies (direct address, subject directory, and search engines) and their reasoning underlying these choices.